2013
DOI: 10.3109/0284186x.2013.822099
|View full text |Cite
|
Sign up to set email alerts
|

The use of an active appearance model for automated prostate segmentation in magnetic resonance

Abstract: Background. The prostate gland is delineated as the clinical target volume (CTV) in treatment planning of prostate cancer. Therefore, an accurate delineation is a prerequisite for efficient treatment. Accurate automated prostate segmentation methods facilitate the delineation of the CTV without inter-observer variation. The purpose of this study is to present an automated three-dimensional (3D) segmentation of the prostate using an active appearance model. Material and methods. Axial T2-weighted magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…For decades, automated segmentation has been investigated enthusiastically. In terms of prostate imaging, Korsager et al reported prostate segmentation with a mean Dice similarity coefficient (DSC) of 0.84 on T2-weighted magnetic resonance imaging (MRI) using a levelset method, which utilized an implicit representation of the contour to be tracked [8]. The DSC is a common index of segmentation accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, automated segmentation has been investigated enthusiastically. In terms of prostate imaging, Korsager et al reported prostate segmentation with a mean Dice similarity coefficient (DSC) of 0.84 on T2-weighted magnetic resonance imaging (MRI) using a levelset method, which utilized an implicit representation of the contour to be tracked [8]. The DSC is a common index of segmentation accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…There are several automatic, and semiautomatic segmentation techniques have been investigated and developed to perform prostate MRI segmentation faster and more reproducible compared to manual contouring [7][8][9][10][11][12][13][14][15][16][17]. Korsager et al [10] presented an automatic segmentation algorithm based on atlas registration combined with intensity and shape information in a graph cut segmentation framework.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have used a combination of shape and intensity information of the prostate to model and segment the prostate. Toth and Madabhushi 17 used image derived features in an active appearance model and Korsager et al 18 used an active appearance model to combine shape and image intensities with a level-set representation of the prostate shape. The use of active shape models and active appearance models has shown to be feasible for MR prostate segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of active shape models and active appearance models has shown to be feasible for MR prostate segmentation. 17,18 However, the underlying assumption that the shape and appearance can be described statistically using a Gaussian distribution might not be valid due to, e.g., large variation between patients. 19 The assumption of Gaussian distributions was addressed by Guo et al 19 by guiding a deformable model by sparse learning methods for both the prostate appearance and for the prostate shape modeling.…”
Section: Introductionmentioning
confidence: 99%